2011
DOI: 10.1161/circgenetics.111.959601
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in the Apolipoprotein(a) Gene and Coronary Heart Disease

Abstract: T wo independent single-nucleotide polymorphisms (SNPs) in the gene encoding apolipoprotein(a) (LPA) have been shown to be associated with coronary heart disease (CHD) and lipoprotein(a) levels in Caucasians. For the missense SNP rs3798220 (Ile4399Met), carriers of 1 or 2 copies of the minor allele (Met) were at 57% increased risk of CHD. For the intronic SNP rs10455872, the risk of CHD increased by 42% for each copy of the minor allele. The rs3798220 SNP was also associated with differential response to asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 66 publications
1
29
2
Order By: Relevance
“…The strongest association was observed for rs10455872 (an intronic SNP) and rs3798220 (a nonsynonymous SNP in the PD) (157). A subsequent meta-analysis of these findings reported that CHD risk in the carriers of the minor alleles of rs10455872 and rs3798220 was increased by 42 and 57%, respectively (217).…”
Section: Snps As Markers For Chd Riskmentioning
confidence: 96%
See 1 more Smart Citation
“…The strongest association was observed for rs10455872 (an intronic SNP) and rs3798220 (a nonsynonymous SNP in the PD) (157). A subsequent meta-analysis of these findings reported that CHD risk in the carriers of the minor alleles of rs10455872 and rs3798220 was increased by 42 and 57%, respectively (217).…”
Section: Snps As Markers For Chd Riskmentioning
confidence: 96%
“…As outlined, GWASs and candidate gene approaches have identified SNPs within LPA associated with CHD (157,196,197,217,218). The question of whether the results of such association studies in one population (i.e., Europeans) are valid for other ethnic groups has recently been addressed for the nonsynonymous SNP, rs3798220 (201).…”
Section: New Phenotypic Associations Of Lp(a)mentioning
confidence: 99%
“…In addition to apo(a) and apoB100, Lp(a) particles also contain apoAI, apoE and traces of apoAII [168]. Single nucleotide polymorphisms in the LPA gene locus and repeat polymorphisms in the promoter region of the LPA gene which increase Lp(a) levels have been shown to be associated with increased CHD risk [169,170]. Further, the risk for CHD increased continuously with a decreasing number of kringle 4 repeats [171].…”
Section: Lipoprotein(a)mentioning
confidence: 99%
“…7B ). OxPLs were clearly present in apo(a) captured from the 17K and 17K ⌬ VP constructs, which are missing KV and KV and the protease domain respectively, the I4399M r-apo(a) construct, which represents the LPA single nucleotide polymorphism (SNP) rs3798220 with an isoleucine to methionine substitution associated with CAD ( 45,46 ) and high OxPL/apoB levels ( 47 ), and human plasma. No OxPLs were detectable on 17K ⌬ Asp 57 r-apo(a) (chimpanzee and gorilla variant) that contains KV but has a substitution of alanine to aspartate 57 on KIV 10 .…”
Section: Identifi Cation Of Oxpls In Human Lp(a) By Lc-ms/msmentioning
confidence: 99%